THE SOCIAL CONTEXT OF GENTRIFICATION IN LAGOS STATE, NIGERIA (2023)
Gentrification, a process of displacement of low-income households and businesses by high-income class, is a disconcerting feature of development in Lagos State. Previous studies on gentrification focused on physical transformations of built environment with little attention paid to its sociological processes. This study, therefore, adopted a sociological approach to investigate the social history, processes, drivers, patterns, costs, adaptive strategies and social relations of gentrification in Lagos State, Nigeria. Gentrification Interpretive Theory provided the framework, while the descriptive research design was adopted. Agege, Alimosho, Oshodi, Eti-Osa, Lagos Mainland and Lagos Island Local Government Areas (LGAs) were purposively selected due to their pervasiveness in gentrification. Primary data were collected using quantitative and qualitative instrumentations, while secondary data were obtained from official documents. Using systematic sampling technique, a total of 894 copies of questionnaire were administered to residents of gentrifying areas based on Cochran’s (1977) formula; 24 In-depth Interviews (four per LGA) were conducted among longtime and new residents, voluntarily displaced landlords and tenants; 24 Key Informant Interviews (four per LGA) were conducted with developers (one per LGA), estate agents (one per LGA), one official of Lagos State Urban Renewal Authority, and another from Lagos State Building Control Agency; six Focus Group Discussions (one per LGA) were held among religious leaders, and six Life Histories (one per LGA) were done among community leaders. The processes and patterns of gentrification were observed through non-participant observation. Quantitative data were analysed using descriptive statistics, Chi-Square and Multiple linear regressions at p≤0.05, while qualitative data were content-analysed. The respondents’ age was 42.41±15.64 years; of whom 62.0% were males and 50.1% earned >N100,000 monthly. Gentrification was traced to the colonial era. It manifested in displacements of low income households and businesses by governments and wealthy individuals through private and government driven processes. The private processes entailed persuasion of poor landlords by gentrifiers through agents, and this was jointly predicted by education, age and income (Adj.R2 = 0.19, F (3, 891) = 73.29). The government-driven processes were characterised by disregard for court injunctions on the legality of occupancy of gentrifying areas. Influx and expansion of businesses (23.6%) and profit-seeking behaviour (34.0%) were generic and specific drivers of gentrification respectively, and these were significantly related to respondents’ income (χ2 =202.42), education (χ2 =237.78) and occupation (χ2 =234.32). While political and criminal gentrifications were new patterns of gentrification in Lagos, homelessness (10.3%) and high cost of living (27.2%) were the social and economic costs. Reliance on family and friends’ networks for support (41.2%) and use of refurbished containers (24.8%) were adaptive strategies adopted by displaced families and businesses. Remaining indigent original occupants of the gentrifying areas felt threatened by the arrival of gentry, causing deep sense of alienation. Gentrification processes adversely influenced social relations between low-income residents who have stayed long and the gentry, with grave implications for sustainable peace and development of urban Lagos. Inclusive social and economic policies that would alleviate poverty and meet housing needs in low-income areas of Lagos State should be formulated